Comparative transcriptome analysis reveals the adaptive mechanisms of halophyte Suaeda dendroides encountering high saline environment - Ma, Panpan; Li, Jilian; Sun, Guoqing; Zhu, Jianbo (Frontiers in Plant Science, 2024)
Suaeda dendroides, a succulent euhalophyte of the Chenopodiaceae family, intermittently spread around northern Xinjiang, China, has the ability to grow and develop in saline and alkali environments. The objective of this study was therefore to investigate the underlying molecular mechanisms of S. dendroides response to high salt conditions. 27 sequencing libraries prepared from low salt (200 mM NaCl) and high salt (800 mM NaCl) treated plants at 5 different stages were sequenced using Illumina Hiseq 2000. A total of 133,107 unigenes were obtained, of which 4,758 were DEGs. The number of DEGs in the high salt group (3,189) was more than the low salt treatment group (733) compared with the control. GO and KEGG analysis of the DEGs at different time points of the high salt treatment group showed that the genes related to cell wall biosynthesis and modification, plant hormone signal transduction, ion homeostasis, organic osmolyte accumulation, and reactive oxygen species (ROS) detoxification were significantly expressed, which indicated that these could be the main mechanisms of S. dendroides acclimate to high salt stress. The study provides a new perspective for understanding the molecular mechanisms of halophytes adapting to high salinity. It also provides a basis for future investigations of key salt-responsive genes in S. dendroides.